2014
DOI: 10.21083/ajote.v3i3.2762
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress: Its Causes and Results at a Ugandan University

Abstract: The study examined academic stress, study habits and academic performance of 196 (113 males and 83 females) undergraduates of Mbarara University of Science and Technology in Uganda using a cross-sectional survey research design. Findings showed that daily academic hassles were found to be the most stressful (M = 3.11; SD = 0.96) while personal problems were reported as the least stressful (M = 2.27; SD = 0.86). First year students experienced greater academic stress from financial hardships (χ 2 = 10.71; p = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
1
27
1
2
Order By: Relevance
“…According to the study of American Health Association that was carried out with 97.357 students in 2006, 32 percent of students consider educational stress as a reason for low grades and dropout [44]. High expectations, information overload, academic pressure, unrealistic ambitions, limited opportunities and high competition are the most common causes of academic stress [33]. Educational stress decreases performance, poses a threat to students' well-being, and causes mental and physical health problems [31].…”
Section: Educational Stressmentioning
confidence: 99%
“…According to the study of American Health Association that was carried out with 97.357 students in 2006, 32 percent of students consider educational stress as a reason for low grades and dropout [44]. High expectations, information overload, academic pressure, unrealistic ambitions, limited opportunities and high competition are the most common causes of academic stress [33]. Educational stress decreases performance, poses a threat to students' well-being, and causes mental and physical health problems [31].…”
Section: Educational Stressmentioning
confidence: 99%
“…According to Nakalema and Ssenyonga (), high expectations, information overload, academic pressure, unrealistic ambitions, limited opportunities, and high competitiveness are some of the more common causes of academic stress among college students. The impact of these factors is exacerbated among 1st‐year students because the adjustment challenges these students face are most prevalent.…”
Section: Academic Stressmentioning
confidence: 99%
“…While these findings show high prevalence of stress, studies done particularly among health professional students in African universities have documented worrying levels of stress ranging from 21.6% to 86% (Amr, El‐Gilany, El‐Moafee, Salama, & Jimenez, ; Dessie, Ebrahim, & Awoke, ; Ofili, Oriaifo, Okungbowa, & Eze, ). In Uganda, data about stress among health professional students are scarce; however, a study done to explore academic stress among students of Mbarara University revealed that students had moderate levels of stress and it affected their academic performance negatively (Nakalema & Ssenyonga, ).…”
Section: Introductionmentioning
confidence: 99%